Transcatheter closure of a residual aorto-left ventricular tunnel: report of a case with a 6-year follow-up. (17th April 2017) - Djukic, Milan; Djordjevic, Stefan A.; Dähnert, Ingo
Abstract: Aorto-left ventricular tunnel is an exceedingly rare congenital cardiac defect. Early surgical closure is the treatment of choice. Residual or recurrent tunnel and aortic valve insufficiency are well-recognised complications after surgical repair. In this article, we report on successful transcatheter closure of a residual aorto-left ventricular tunnel using an Amplatzer duct occluder in a 7-year-old boy. The outcome after 6 years of follow-up is encouraging.